Association between parenting styles and dyslexia in primary school students: the mediating role of home literacy environment - Wen, Wanyi; Zhang, Xuanzhi; Wu, Kusheng; Guan, Liwen; Huang, Anyan; Liang, Zhiya; Yu, Xinle; Gu, Qianfei; Huang, Yanhong (Frontiers in Psychology, 2024)
Background Despite an increasing amount of research on the relationship between parenting styles and neurodevelopmental disorders, there has been minimal focus on how parenting styles impact children’s reading abilities. The aim of this study was to investigate the potential mediating role of the home literacy environment in the connection between parenting styles and dyslexia. Methods A total of 212 primary school students from grade 2–5 were recruited for this study. The Chinese Reading Ability Test was used to screen children with dyslexia. The home literacy environment was evaluated using a structured questionnaire that measured the frequency and quality of reading-related activities between parents and children. Egna Minnen Beträffande Uppfostran questionnaire was used to assess the parenting style, including emotional warmth, rejection, overprotection, and anxious rearing. It is a self-report tool filled out by the children themselves, used to assess their perceptions of their parents’ parenting styles. The structural equation modeling was carried out to evaluate the direct, indirect, and total effects of parenting styles on dyslexia. Results Compared to control group, male children with dyslexia had lower scores in parenting styles characterized by emotional warmth, overprotecting and anxious rearing (p < 0.05), while female children with dyslexia only showed lower scores in anxious rearing (p < 0.05). Children with dyslexia lacked regular reading time (OR = 2.69, 95%CI: 1.04–6.97, p < 0.05), and have higher homework pressure compared to normal children (OR = 7.41, 95%CI: 1.45–37.82, p < 0.05). Additionally, emotional warmth, paternal overprotection and anxious rearing were negatively associated with dyslexia in children (all p < 0.05). Our findings indicate a strong correlation between dyslexia, home literacy environment, and parenting styles. In a structural equation model, the home literacy environment was identified as an independent mediator between parenting styles and dyslexia. The total effect of parenting styles on dyslexia is 0.55, with an indirect effect of 0.68 mediated by the home literacy environment. Conclusion The findings of this study indicate that home literacy environment serves as a mediator between parenting styles and dyslexia in children. This study highlights how parenting styles influence dyslexia, offering key insights for aiding dyslexic children and guiding effective interventions.